A Case of Pancreatic Cancer as a Recurrence of Intraductal Papillary Mucinous Neoplasm Following Surgical Resection - Choi, Sae Byeol; Jo, Hye Sung; Choi, Sang Yong (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Serial TC changes.